2014
DOI: 10.1039/c4cc01646g
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of nanocrystalline transition metal oxides on thin sheets of disordered graphitic carbon by oxidation of MXenes

Abstract: Herein we show that heating 2D Ti3C2 in air results in TiO2 nanocrystals enmeshed in thin sheets of disordered graphitic carbon structures that can handle extremely high cycling rates when tested as anodes in lithium ion batteries. Oxidation of 2D Ti3C2 in either CO2 or pressurized water also resulted in TiO2-C hybrid structures. Similarly, other hybrids can be produced, as we show here for Nb2O5/C from 2D Nb2C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
424
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 661 publications
(484 citation statements)
references
References 36 publications
(47 reference statements)
41
424
0
Order By: Relevance
“…43 The increased intensities of D-and G-bands in Ti 3 C 2 /TiO 2 composites might indicate the formation of carbon. 38 XPS analyses were carried out to characterize the elemental composition of the prepared samples, as shown in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…43 The increased intensities of D-and G-bands in Ti 3 C 2 /TiO 2 composites might indicate the formation of carbon. 38 XPS analyses were carried out to characterize the elemental composition of the prepared samples, as shown in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%
“…Among the transition metal oxides, titanium dioxide (TiO 2 ) is one of the most widely investigated electrode materials, owing to its low cost, abundant availability and convenient synthesis in nanoscale sizes. [34][35][36][37] Many studies have reported different preparation methods to introduce TiO 2 into the two-dimensional MXenes layers, such as heat treatment of MXenes sheets, [38][39][40] in situ hydrolysis 31 and traditional hydrothermal process 5 . For example, C. J. Zhang et al fabricated TiO 2 @ Ti 3 C 2 T x composite via heating Ti 3 C 2 T x powders in flowing CO 2 for 1 h at 500…”
mentioning
confidence: 99%
“…It is been reported by density functional theory (DFT) calculations that pure MXene has higher theoretical capacitance in Li-ion batteries than those which has surface terminations [9][10]. It was shown that heat treatment of MXene can tune the surface termination in this material and can improve the volumetric capacitance [11][12]. The TiO 2 /C composite (the composite based on TiO 2 particles in amorphous carbon matrix) shows a good performance as an electrode material for Li-ion battery anodes.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42] Therefore, combining Ti 3 C 2 T x /TiO 2 and co-catalyst such as LDHs is expected to produce high performance PEC photocatalyst.…”
Section: -39mentioning
confidence: 99%